Ballistic limit prediction on nacre shell using numerical simulation approach - Abdul Rahman, Muhammad Faisal; Kamarudin, Kamarul Azhar; Dahlan, Hendery; Mohamed Hattab, Mohamed Nasrul (FAZ Publishing, 2020)
An investigation has been carried out to predict the ballistic limit velocity for blunt and hemispherical projectile using mesh sensitivity technique analysis. The finite element simulation is done using ANSYS Explicit Dynamics software. The Drucker-Prager material model is employed to predict the ballistic limit velocity since it is suitable for brittle material properties. Meshing with various cube element sizes are used to predict the ballistic limit velocity for projectiles. The initial impact velocity is set at 50m/s to obtain the graph of residual velocity against a number of the element for the blunt and hemispherical projectile. The stable mesh sizing for blunt projectile is taken at residual velocity of 43.82m/s, while the stable mesh sizing for hemispherical projectile is taken at residual velocity of 44.47m/s. The results of ballistic limit velocity for blunt and hemispherical projectiles are 7.5m/s and 12.5m/s respectively. The ballistic limit velocity for hemispherical projectile is 10% higher than the blunt projectile, due to the hemispherical projectile tensile damage whereas the blunt projectile created a shear failure.